(3GdefgL GdeSdhc aj SjGSI Gdedhcs - (3YHO GdQMef Hf fUQ Hf YHO Gddg, CHh GdfLjH, LdGd GdOjf GdYOhj GdTjRQj, fMh (B590 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi YLRJ GdYbhd Yf eYQaI PGJg bGd YHO GdQMef LeYJ dNRGfI Ydheg gPG GdcJGH jMJhi Ydi WQGja ef GdMceg hCUhd ai GdSjGSI s
(3BNQgG (B:s
(3bGd di GdQTjO EPG OddJfi Ydi QLd aOdfi Ydi eKd gPG agPG Gdjhe SjO GdeSdejf hbO GfJgjfG s
(3Cdag dCHh GdeXaQ jhSa Hf CjhH Hf TGOi eMi Ohdg CejQ GdeDefjfs
(3fSNI QGHYIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B340 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B197s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3GdSjGSI hGdGLJeGYs